2013
DOI: 10.1111/cpr.12035
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic differentiation of adipose‐derived stem cells prompted by low‐intensity pulsed ultrasound

Abstract: We successfully demonstrated that LIPUS enhanced osteogenesis of ASCs, specially at the duty ratio of 20%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…PCA and heat map clustering analyses of the obtained proteomic data, suggested that the most significant differences in protein expression profiles of MSCs are due to the specific growth medium (MSCGM or OM) rather than the exposure to LIPUS. Very few studies were focused indeed on osteogenic differentiation of hMSC (Gao, Walmsley, Cooper, & Scheven, ; Hu et al, ; Yue et al, ) mediated by LIPUS treatment. In this sense, our proteomics analysis revealed the existence of differences in osteoblast commitment and differentiation potential between all experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…PCA and heat map clustering analyses of the obtained proteomic data, suggested that the most significant differences in protein expression profiles of MSCs are due to the specific growth medium (MSCGM or OM) rather than the exposure to LIPUS. Very few studies were focused indeed on osteogenic differentiation of hMSC (Gao, Walmsley, Cooper, & Scheven, ; Hu et al, ; Yue et al, ) mediated by LIPUS treatment. In this sense, our proteomics analysis revealed the existence of differences in osteoblast commitment and differentiation potential between all experimental groups.…”
Section: Discussionmentioning
confidence: 99%
“…Then the suspension was added into plates or T25 flasks at 37°C in a humidified atmosphere of 5% CO 2 . Purified ASCs should be subcultured to passage 2 for further experiments …”
Section: Methodsmentioning
confidence: 99%
“…However, TO could cause erosion of PDL fibre and promote the entry of inflammatory cells into periodontal tissues, thereby accelerating the destruction of periodontal support tissues (Ramfjord & Ash, ; Svanberg et al., ). Our previous in vitro studies showed that mechanical stimulations affected the osteogenic ability of adipose‐derived stem cells and myelinization potential of Schwann cells (Yue et al., , ).…”
Section: Discussionmentioning
confidence: 99%